Theory and practice of foreign aid - Lahiri, Sajal (Frontiers of economics and globalization ;, 2006)
The analysis of the transfer paradox has evolved primarily in the context of traditional static models. However, given developments in the policy arena as well in the discipline itself, there is a need for further developments in the theoretical analysis of foreign aid. For example, the impact of aid on saving, investment and growth calls for an intertemporal framework. Development spatial economics calls for introduction of the spatial dimension to the analysis of foreign aid. Similarly, the potential role of aid in conflict resolution, in improving the environment, in public good (infrastructural) provision, in the globalization process, and in the establishment of good governance are some of the issues that also need serious attention. On the empirical side, the issue of the effectiveness of aid; the determinants of aid; the allocation criteria for aid; the relationship between aid and trade, and aid and poverty remain as important as ever.This volume contains a comprehensive analysis of foreign aid from both theoretical and empirical perspectives, written by leading researchers in the field. It is divided into two parts: Theory of Aid and Empirical Studies on Aid. It examines aid practices in a variety of countries and under a variety of conditions.